Bone marrow adipose tissue is a unique adipose subtype with distinct roles in glucose homeostasis - Suchacki, Karla J.; Tavares, Adriana A. S.; Mattiucci, Domenico; Scheller, Erica L.; Papanastasiou, Giorgos; Gray, Calum; Sinton, Matthew C.; Ramage, Lynne E.; McDougald, Wendy A.; Lovdel, Andrea; Sulston, Richard J.; Thomas, Benjamin J.; et al. (Nature communications, 2020)
Bone marrow adipose tissue (BMAT) comprises >10% of total adipose mass, yet unlike white or brown adipose tissues (WAT or BAT) its metabolic functions remain unclear. Herein, we address this critical gap in knowledge. Our transcriptomic analyses revealed that BMAT is distinct from WAT and BAT, with altered glucose metabolism and decreased insulin responsiveness. We therefore tested these functions in mice and humans using positron emission tomography-computed tomography (PET/CT) with 18 F-fluorodeoxyglucose. This revealed that BMAT resists insulin- and cold-stimulated glucose uptake, while further in vivo studies showed that, compared to WAT, BMAT resists insulin-stimulated Akt phosphorylation. Thus, BMAT is functionally distinct from WAT and BAT. However, in humans basal glucose uptake in BMAT is greater than in axial bones or subcutaneous WAT and can be greater than that in skeletal muscle, underscoring the potential of BMAT to influence systemic glucose homeostasis. These PET/CT studies characterise BMAT function in vivo, establish new methods for BMAT analysis, and identify BMAT as a distinct, major adipose tissue subtype. Bone marrow adipose tissue (BMAT) comprises over 10% of total fat mass but its systemic metabolic role is unclear. Here, the authors show that BMAT glucose uptake is not insulin or cold responsive; however, BMAT basal glucose uptake is higher than in white adipose tissue or skeletal muscle, underscoring BMAT’s potential to influence systemic glucose homeostasis.